Mechanism of TiO2 nanotube UV-photocatalytic degradation of antibiotic resistance genes in the wastewater sludge and blocking of the transfer - Yu, Hang; Zhang, Xu; Zhao, Jingyi; Sun, Tiantian; Zhu, Yimin (Frontiers in Environmental Science, 2025)
Antibiotic resistance genes (ARGs) in sludge propagate via horizontal gene transfer (HGT), necessitating advanced mitigation strategies. This study demonstrates TiO2 nanotube UV photocatalysis effectively degrades ARGs (70.6–82.5% reduction) and suppresses HGT by targeting mobile genetic elements (MGEs; 93.4–97.1% removal). Hierarchical TiO2 nanotubes (anatase phase) generated reactive oxygen species (ROS) inducing oxidative DNA damage and cell lysis, preferentially eliminating intracellular ARGs (33.5–46.6% decline) while converting them to extracellular forms. Mobile genetic elements (MGEs) (tnpA-04/intI1) were selectively fragmented via ROS, outperforming HOCl-based systems. Microbial analysis revealed Proteobacteria (e.g., Kofleria) as key ARG hosts, whose decline correlated with resistance reduction (p<0.05). Radiation-resistant Deinococcus dominated post-treatment communities but lacked ARG associations, indicating non-transmissible residual risks. Spatial-specific degradation mechanisms emerged: UV directly fragmented chromosomal ARGs, while ROS oxidized plasmid-borne MGEs, achieving dual ARG elimination and HGT blockade. The intracellular-to-extracellular ARG shift and host-MGE decoupling confirmed transmission disruption. This work establishes TiO2 photocatalysis as a paradigm for sludge treatment, synchronizing ARG removal and environmental risk mitigation through ROS-microbe-DNA interplay.